THU0137 Associated with A Glucocorticoid Bridging Scheme, Methotrexate is as Effective Alone as in Combination with Other DMARDS for Early Rheumatoid Arthritis, with Fewer Reported Side Effects: 16 Weeks Remission Induction Data from the Carera Trial. (10th June 2014) - Verschueren, P.; De Cock, D.; Corluy, L.; Joos, R.; Langenaken, C.; Taelman, V.; Raeman, F.; Ravelingien, I.; Vandevyvere, K.; Lenaerts, J.; Geens, E.; Geusens, P.; et al.
Abstract : Background: In line with the window of opportunity theory, intensive DMARD combination therapy with glucocorticoids (GCs) is probably the most effective treatment approach for early Rheumatoid Arthritis (eRA), but the ideal content of the combination and the dose of GCs is not yet known. Objectives: To compare the efficacy and safety of intensive treatment strategies associated with GCs at week (W)16, focusing on high risk patients. Methods: CareRA is a prospective two-year investigator-initiated multicenter RCT rooted in daily practice. In this trial, 400 DMARD naïve eRA patients were stratified into high or low risk according to classical prognostic markers such as the presence of erosions, RF/ACPA and disease activity. High risk patients were randomized to 1/3 treatment strategies: COBRA Classic (MTX+ Sulphasalazine + 60mg GCs tapered to 7.5mg daily from W7), COBRA Slim (MTX + 30mg GCs tapered to 5 mg from W6) and COBRA Avant-Garde (MTX + Leflunomide + 30mg GCs tapered to 5 mg from W6). Treatment modifications to target low disease activity were mandatory from W8 onwards, if desirable and feasible according to the rheumatologist. The primary outcome was remission (DAS28(CRP) <2.6) at W16 (ITT analysis). Secondary endpoints were good EULAR response, clinically meaningful HAQ response and HAQ=0. Area under the curve (AUC) for DAS28(CRP) and proportion of treatment adaptations and GC injections were calculated. Adverse events (AEs) were registered. Missing data were imputed by the maximum likelihood method. Results: 290 patients were stratified as high risk: 98 Classic, 98 Slim and 94 Avant-Garde patients. Remission was achieved in 70.4% COBRA CLASSIC patients, 73.5% COBRA SLIM patients, 68.1% COBRA AVANT-GARDE patients (p=0.713) at W16. No significant differences between groups were shown in the proportion with a good EULAR response, clinically meaningful HAQ response and HAQ=0 (all p>0.05). The AUC for DAS28(CRP) in the 3 treatment arms was equal (p=0.521). No difference in treatment adaptions or GCs injections was found at W16.Until W16, therapy related AEs were reported in 61.2% of Classic, in 46.9% of Slim and in 69.1% of Avant-Garde patients (p=0.006). Conclusions: At W16, MTX associated with a moderate step-down dose of GCs was as effective as DMARD combination therapies with moderate or even high step down GC doses in high-risk eRA. The short-term safety profile of MTX with GCs alone was more favorable. Disclosure of Interest: : None declared DOI: 10.1136/annrheumdis-2014-eular.2137